Modifiable dementia risk factors and AT(N) biomarkers: findings from the EPAD cohort - Roccati, Eddy; Bindoff, Aidan David; Collins, Jessica Marie; Eastgate, Joshua; Borchard, Jay; Alty, Jane; King, Anna Elizabeth; Vickers, James Clement; Carboni, Margherita; Logan, Chad, EPAD Consortium (Frontiers in Aging Neuroscience, 2024)
Modifiable risk factors account for a substantial proportion of Alzheimer's disease (AD) cases and we now have a discrete AT(N) biomarker profile for AD biomarkers: amyloid (A), p-tau (T) and neurodegeneration (N). Here, we investigated how modifiable risk factors relate to the three hallmark AT(N) biomarkers of AD. Participants from the European Prevention of Alzheimer's Dementia (EPAD) study underwent clinical assessments, brain magnetic resonance imaging and cerebrospinal fluid collection and analysis. Generalized additive models (GAMs) with penalized regression splines were modelled in AD Workbench on the NTKApp. A total of 1434 participants were included (56% female, 39% APOE ε4+) with an average age of 65.5 (± 7.2) years. We found that modifiable risk factors of less education (t = 3.9, p <0.001), less exercise (t = 2.1, p = 0.034), traumatic brain injury (t = -2.1, p = 0.036) and higher body mass index (t = -4.5, p <0.001) were all significantly associated with higher AD biomarker burden. This cross-sectional study provides further support for modifiable risk factors displaying neuroprotective associations with the characteristic AT(N) biomarkers of AD.